Aislamiento de las funciones contables por falta de experiencia del personal de la empresa Lopatrucks - Garcia Delgado, Angela Jaqueline (2021)
Accounting is a fundamental part of a company because it not only measures the control of accounting and administrative operations but also allows analyzing the performance, liquidity and profit that the company obtains at the end of each period, generating necessary information to the representatives of the company. The accounting functions help to determine how the operations are being carried out within the institution, however in the company Lopatrucks SA of the city of windows there is a lack of communication between the departments reflecting the lack of experience of the collaborators when carrying out a task. The development of this research allowed the owners of the company to make decisions about the aspects that are affecting the growth and fulfillment of objectives and goals, considering in this way the importance of helping their work team in all tasks. Existing departmental areas in the company for a better operation, and thus avoid errors that have been raised with the employees.